Factors Affecting the Growthand Development of Plants in the Drawings of 6. Class Students - Aslı Öztürk; Aysun Öztuna Kaplan (Sakarya University Journal of Education)
Concepts have an important in science teaching. One of the aims of science education is to ensure that students learn meaningfully without memorizing these concepts and use them in their lives in accordance with their needs. Taking into account whether students have conceptual misconceptions when concept teaching is done, will increase the efficiency of teaching. One of the techniques to understand what students understand about concepts, how they reflect on their minds, and whether there are misconceptions is drawing. Drawing is an open technique that does not place limits on how the student will respond, except for small limitations. The purpose of drawings is also to provide the situations in which the teachers can not reveal the other meaning through the methods of examination. The aim of this research is to reveal the knowledge about the factors that influence the growth and development of plants in 6th grade students' science courses and, if so, the misconceptions of the concepts through drawings. For this purpose, students were asked to describe the factors that affect the growth of plants, through drawings, before the 6th grade “Plant and Animal Reproduction, Growth and Development” unit was processed and after the unit was processed. But, individual interviews on student drawings set off secondary data collection source. There search group consists of 23 students who are studying in 6th grade in a state secondary school located in the province of Hendek in Sakarya province. It was seen that the students mostly included drawings of water, sun and fertilizer, two students reflected oxygen in their drawings, but no students had carbon dioxide. As a result, it confirmed that the students reflected on water and light their drawings from the elements necessary for growth of plants, and some misconceptions were found in drawings.